Hegemony machines documenta X to fifteen and the politics of biennalization - Marchart, Oliver 1968- (OnCurating.org, 2022)
In his essay Oliver Marchart takes an analytical and provocative look at the last six documenta exhibitions. Based on the theories of Antonio Gramsci, Ernesto Laclau and Chantal Mouffe, Marchart describes museums and biennials as national and global hegemony machines that reproduce bourgeois dominant culture, but also make it vulnerable to attack. Along with documenta’s recent history, Marchart traces a canon shift in the art field with regard to political art practices, theory, art education and the decentering of the West
Rückseite Titelblatt: This publication is a translated and extended version of "Hegemonie im Kunstfeld. Die documenta-Ausstellungen dX, D11, d12 und die Politik der Biennalisierung" by Oliver Marchart, published by Marius Babias, neuer Berliner Kunstverein (n.b.k.) as volume 2 of the series n.b.k. Diskurs, © 2008
Keywords: Documenta; Geschichte 1997-2007; Hegemonie; Großveranstaltung; Kunstbetrieb; Art / Political aspects; Art, Modern / Exhibitions; Hegemony